Cycling coaches` trauma-specific education, familiarity with post-traumatic stress, and coaching efficacy - Leibovitz, A. P.; Martin, S. B. (International Journal of Sports Science & Coaching, 2022)
The primary purpose of this study was to assess cycling coaches` trauma-specific education and familiarity with post-traumatic stress (PTS). A secondary purpose was to examine the relation between trauma-specific education, familiarity with PTS, and coaching efficacy specific to coaching trauma-impacted athletes, after controlling for general coaching experience. Descriptive statistics indicated that most coaches lacked trauma-specific education but reported a relatively high degree of familiarity with PTS. Hierarchical regression analyses indicated that familiarity with PTS helped to explain additional variance in coaching efficacy over and above demographic and general coach experience variables. Findings indicate that trauma-informed coaching appears to be a distinct area of research and highlights the need for improved continuing education opportunities for coaches related to psychological trauma and PTS.